Composite for secondary battery electrode

The composite for secondary battery electrodes addresses the challenge of uniform fibrous carbon distribution by using partially crushed and aggregated fibrous carbon, resulting in improved conductivity and reduced resistance, thereby enhancing battery performance.

JP2025009664APending Publication Date: 2025-01-20TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023172999
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for producing secondary battery electrodes face challenges in uniformly distributing fibrous carbon nanotubes, leading to non-uniform conductive networks and increased electrode resistance, which hinders the formation of efficient conductive paths and reduces battery capacity.

Method used

A composite for secondary battery electrodes is developed, where fibrous carbon is partially crushed and adheres to the surface of the active material, forming aggregates with specific particle sizes and distributions, ensuring uniform dispersion and reduced resistance.

Benefits of technology

The composite achieves high conductivity, lowers electrode resistance, and improves battery rate and cycle characteristics by forming efficient conductive paths with a reduced amount of conductive aid, enhancing battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009664000001_ABST
    Figure 2025009664000001_ABST
Patent Text Reader

Abstract

To provide a composite for a secondary battery electrode capable of acquiring high conductivity even in electrodes by a compounding method using an active material and fibrous carbon.SOLUTION: A composite for a secondary battery electrode contains an electrode active material and fibrous carbon, where a part of the fibrous carbon has a crushed form and adheres to the surface of the electrode active material, and a part of the fibrous carbon has an aggregate form. A method for producing the composite for a secondary battery electrode comprises a step of using a mixing device to combine an electrode active material with a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent, and a step of removing the solvent and drying.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite for a secondary battery electrode, and an electrode, a secondary battery, and a device each using the composite. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] The electrodes of secondary batteries are prepared by coating a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc., on a current collector. A conductive material dispersion liquid in which a conductive material is dispersed in a dispersion medium is prepared, and an active material and a binder resin are added to the conductive material dispersion liquid to prepare a composite slurry, so that the conductive material is uniformly dispersed and contained in the electrode film, and the conductivity of the electrode film can be improved. In order to increase the capacity of secondary batteries, an increase in the ratio of active materials in the electrodes is desired, and carbon nanotubes, which can efficiently form a conductive network even with a small amount as a conductive agent and reduce electrode resistance, are considered promising. On the other hand, in order to achieve low resistance with the addition of a smaller amount of carbon nanotubes, it is effective to use carbon nanotubes with a small average outer diameter and large fiber length. However, these carbon nanotubes have strong cohesive forces, making it difficult to distribute them uniformly in the electrode. In order to efficiently form a conductive network in the electrode and ensure a conductive path to the active material, a method has been proposed in which a composite is used in which a conductive material such as carbon nanotubes is adsorbed onto the surface of the active material in advance.

[0004] Patent Document 1 discloses an example in which a positive electrode active material and acetylene black are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. Patent Document 2 discloses an example of producing composite particles with excellent particle strength by spray granulating a slurry containing a positive electrode active material, carbon black, and cellulose nanofibers. Patent Document 3 discloses an example of producing a positive electrode active material with high electronic conductivity and high mechanical strength by compounding a positive electrode active material and carbon nanotubes by mechanochemical treatment under a nitrogen atmosphere. Furthermore, Patent Document 4 discloses an example in which positive electrode active material particles and fibrous carbon are dispersed in a solvent using an ultrasonic disperser, and the resulting slurry is spray-granulated to produce composite particles in which the materials are uniformly mixed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-201228 A [Patent Document 2] Patent No. 6380526 [Patent Document 3] JP 2017-142997 A [Patent Document 4] Patent No. 5377946 Summary of the Invention [Problem to be solved by the invention]

[0006] In the methods disclosed in Patent Documents 1 and 2, a dispersion of acetylene black is used as a conductive assistant, and therefore, compared to the case where fibrous carbon is used as a conductive assistant, a small amount of the additive is more efficient. However, it is difficult to form a conductive network. In the method disclosed in Patent Document 3, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite formation process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in a non-uniform composite, making it difficult to form a uniform conductive network in the electrode. In the method disclosed in Patent Document 4, the carbon nanotubes are present in the composite particles in a loose mesh state, and therefore, when used to form an electrode, the formation of conductive paths between the composite particles is insufficient.

[0007] In order to solve the above problems, an object of the present invention is to provide a composite for a secondary battery electrode that can obtain high electrical conductivity even in the electrode by a composite method using an active material and fibrous carbon. [Means for solving the problem]

[0008] The present invention relates to a composite for a secondary battery electrode comprising an electrode active material and fibrous carbon, characterized in that a portion of the fibrous carbon has a crushed form and is attached to a surface of the electrode active material, and a portion of the fibrous carbon has an aggregate form.

[0009] The present invention relates to the composite for a secondary battery electrode, wherein the average particle size of the aggregates is from 0.2 μm to 50 μm.

[0010] The present invention relates to the above composite for a secondary battery electrode, wherein the fibrous carbon has an exothermic peak temperature of 550° C. or less as measured by simultaneous thermogravimetry-differential thermal analysis in the presence of oxygen.

[0011] The present invention relates to the above composite for a secondary battery electrode, further comprising a binder resin.

[0012] The present invention also relates to an electrode for a secondary battery comprising the above-mentioned composite for a secondary battery electrode.

[0013] The present invention relates to a secondary battery including the secondary battery electrode.

[0014] The present invention relates to a vehicle or device equipped with the secondary battery.

[0015] The present invention provides a method for producing the above-described composite for a secondary battery electrode, comprising the steps of: The present invention relates to a method for producing a composite for a secondary battery electrode, comprising the steps of: combining a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent with an electrode active material using a mixing device; and removing the solvent and drying the resulting composite. Effect of the Invention

[0016] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing aggregates of fibrous carbon in the composite of Example 1-1 by SEM. [Diagram 2] FIG. 2 is an enlarged view taken by SEM showing a state in which the fibrous carbon in the composite in Example 1-1 is adsorbed on the surface of the active material and crushed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the gist of the present invention is not changed. Also included are embodiments implemented in the above-mentioned range.

[0019] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."

[0020] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material and fibrous carbon, and may further contain an optional dispersant and a binder resin. The composite for an electrode may further contain optional components.

[0021] The fibrous carbon contained in the electrode composite of the present invention is partly in a crushed form and adheres to the surface of the active material, and partly in an aggregate form.

[0022] It is important for the fibrous carbon to have the above two morphologies in order to realize excellent battery characteristics. The presence of the fibrous carbon in a crushed form on the surface of the active material allows the active material to efficiently receive electrons required for the battery reaction, and the inclusion of the fibrous carbon in an aggregate form in the composite allows the contact resistance between the active materials to be reduced when an electrode is fabricated. Therefore, if the fibrous carbon is crushed and uniformly adsorbed on the surface of the active material, and if the fibrous carbon contains aggregates of an appropriate particle size and number, when the fibrous carbon is used as an electrode for a secondary battery, the electrode resistance is reduced, and the formation of an electronic conduction path to the active material during the battery reaction is favorable, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.

[0023] The crushed form of fibrous carbon refers to a form in which secondary particles (aggregates) of fibrous carbon are broken down into primary particles or a bundle state in which multiple primary particles are bundled together. The state in which fibrous carbon is crushed and adsorbed onto the active material surface includes a state in which the primary particles and / or bundles are isolated, and a state in which the primary particles and / or bundles are overlapped. From the viewpoint of electron supply to the active material and conductive paths between composites, a state in which the primary particles and / or bundles are overlapped and adsorbed in a mesh-like shape is preferred.

[0024] In the present invention, the state in which the fibrous carbon is adsorbed on the surface of the active material in a crushed form means that the area of ​​the fibrous carbon adsorbed on the active material in a crushed fiber state is 10% or more of the entire surface of the active material, preferably 20% or more, and more preferably 50% or more.

[0025] The area occupied by the fibrous carbon adsorbed to the active material in the crushed fiber state can be measured from the contrast difference between the active material and the fibrous carbon in images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average value of the above areas calculated from 20 pieces of active material in the composite was used.

[0026] The fibrous carbon aggregate in the present invention is an aggregate having a morphology in which primary particles of fibrous carbon and / or bundles of a plurality of primary particles are entangled.

[0027] The particle diameter of the fibrous carbon aggregates in the present invention can be measured from the length of the long axis of the fibrous carbon aggregates from images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average particle diameter of 10 fibrous carbon aggregates was taken as the average particle diameter of the aggregates.

[0028] The aggregate of fibrous carbon in the present invention refers to one having an average particle size of 0.1 to 100 μm, preferably 0.2 to 10 μm, more preferably 0.2 to 5 μm, and even more preferably 0.2 to 3 μm. If there are aggregates of fibrous carbon having an average particle size of more than 100 μm, it may be difficult to form a uniform composite.

[0029] The number of aggregates of the fibrous carbon in the present invention can be measured from the average number of aggregates of the fibrous carbon measured from 10 observation images (observation field area 20 μm×15 μm) taken at a magnification of 5,000 times by a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). The average number of aggregates of the fibrous carbon in the present invention is preferably 1 or more.

[0030] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 550° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.

[0031] The temperature of the exothermic peak in the present invention is measured by TG-DTA (Thermo Gravimetry-Diastereometry). The temperature can be determined by a differential thermal analysis (TG-DTA) measurement. Specifically, a TG curve and a DTA curve are obtained by performing a TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the top of the exothermic peak of the fibrous carbon, which is located in the vicinity of 300 to 600°C, is read and regarded as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the decomposition temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.

[0032] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 550°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.

[0033] When the volume resistivity of the electrode composite for secondary batteries is 500 Ω·cm or less under a load of 20 kN, the fibrous carbon in the composite is not unevenly distributed and is adsorbed on the active material in a more uniform state, which reduces the electrode resistance when used as a secondary battery electrode. A volume resistivity of 100 Ω·cm or less is preferable, and 50 Ω·cm or less is more preferable.

[0034] The volume resistivity of the electrode composite for secondary batteries can be determined by performing resistivity measurement based on the four-terminal four-probe method. Specifically, four needle-like probes (electrodes) are brought into contact with the composite for secondary battery electrodes to be measured, and the resistance of the test piece is calculated from the current flowing between the two outer probes and the potential difference generated between the two inner probes. The volume resistivity of the CNTs can then be calculated from the measured resistance and the thickness of the test piece. The measurement is performed using a volume resistivity measuring device (for example, the low-resistance version of the automatic powder resistivity measuring system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd.) under a load of 20 kN.

[0035] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.

[0036] As mentioned above, when the combustion temperature is 550°C or less and the volume resistivity is 100 Ω·cm or less, the fibrous carbon in the composite is crushed and is adsorbed thinly and uniformly on the active material, making it suitable for use in secondary batteries. When used as an electrode, it is preferable because it reduces the electrode resistance and is advantageous in forming an electron conduction path to the active material during the battery reaction, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.

[0037] <Active material> The active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. For example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used as the positive electrode active material. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxide (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt composite oxide (e.g. Lix Ni 1-y Co y (O2), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y (O2), lithium nickel manganese cobalt composite oxide (e.g., Li x Ni y Co z Mn 1-y-z (O2), spinel-type lithium manganese nickel composite oxide (e.g., Li x Mn 2-y Ni y (O4), etc., composite oxide powders of lithium and transition metals, lithium phosphate powders having an olivine structure (e.g., Li x FePO4, Li x Fe 1-y Mn y (PO4), Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxides (e.g., V2O5, V6O 13 )), transition metal oxide powders such as titanium oxide, iron sulfate (Fe2(SO4)3), transition metal sulfide powders such as TiS2, and FeS, etc. Here, x, y, z are numbers, 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < y + z < 1. These cathode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to be highly basic due to elution of components derived from raw materials or metal ions, and due to this influence, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.

[0038] As the negative electrode active material, for example, metallic Li capable of reversibly doping or intercalating lithium ions, or its alloy, tin alloy, silicon-based material (such as metallic Si, Si alloy, SiOx, etc.), metal oxide-based materials such as LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2, conductive polymers such as polyacetylene, poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.

[0039] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, having a high aspect ratio in the long axis direction, and it is easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNT has a shape in which planar graphite is wound into a cylindrical shape, including single-walled CNT, double-walled CNT, thin-layer (several layers) CNT, multi-walled CNT, and these may be mixed. Single-walled CNT has a structure in which one layer of graphite is wound. Multi-walled CNT has a structure in which two or more layers of graphite are wound. Also, the side wall of CNT does not have to be a graphite structure. Also, for example, CNT having a side wall with an amorphous structure is also CNT in this specification.

[0040] The shape of CNT is not limited. Such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stacking type), platelet-like (platelet), and coil-like. Among them, the shape of CNT is preferably needle-like or cylindrical tube-like. CNT may be in a single shape or a combination of two or more shapes.

[0041] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.

[0042] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it may be difficult to uniformly combine with the composite. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. Also, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.

[0043] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.

[0044] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.

[0045] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Particularly, fluororesins are preferred, and examples thereof include polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and modified products thereof. These may be used alone or in combination of two or more. Among these, polymers having fluorine atoms in the molecule are preferred from the viewpoint of resistance. Among these, preferred are copolymers or copolymers such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, resins having these structural units, and modified products thereof.

[0046] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0047] <Method of manufacturing a composite for secondary battery electrode> The method for compounding the positive electrode active material with the fibrous carbon or the like is not particularly limited. For example, there may be mentioned a method of mixing the active material and fibrous carbon etc. in a dry state, a method of further mixing by adding a solvent, a method of mixing using a dispersion liquid in which the active material and fibrous carbon etc. are dispersed in a solvent, a method of mixing the active material, fibrous carbon etc. and a solvent to prepare a slurry, and a method of mixing the active material, fibrous carbon etc. and a solvent in a wet state. In order to prepare a more uniform composite, a method of mixing using a dispersion liquid in which fibrous carbon or the like is dispersed in a solvent in advance is preferred. Among them, the use of a fibrous carbon dispersion is preferred because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Even if a fibrous carbon dispersion is not used, it is preferred because the same effect can be obtained by breaking up the agglomerates of the fibrous carbon using a high shear force composite machine or the like. In particular, in order to prepare an excellent composite in the present invention, a method of combining the active material and the fibrous carbon dispersion using a high shear force composite machine under non-slurry conditions of high concentration and lack of fluidity is preferred.

[0048] Examples of dry mixers include: Examples of such equipment include roll mills with two or three rolls, high-speed agitators such as Henschel Mixers and Super Mixers, fluid energy grinders such as Micronizers and Jet Mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro," mixers manufactured by Inoue Manufacturing Co., Ltd. such as "Planetary Mixer" and "Trimix," and mixer / granulator "High Speed ​​Mixer" manufactured by EarthTechnica.

[0049] In addition, when using a dry mixer, other raw materials such as fibrous carbon may be added directly in powder form to the active material as the base material, but in order to create a more uniform mixture, it is preferable to disperse or dissolve the other raw materials such as fibrous carbon in a small amount of solvent in advance and then mix them. Among these, the use of a fibrous carbon dispersion is preferable because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Furthermore, in order to increase the processing efficiency, it may be preferable to heat the mixture. Among dry mixers, a planetary mixer, trimix, or mechanofusion, which is capable of compounding by shearing, is preferable.

[0050] Examples of wet mixing devices include: Mixers such as dispersers, homomixers, or planetary mixers; Homogenizers such as "Clearmix" manufactured by M Techniques or "Filmix" manufactured by PRIMIX; Rotation and revolution type mixers such as THINKY's "Awatori Rentaro" Media-type dispersing machines such as a paint conditioner (manufactured by Red Devil), a ball mill, a sand mill (such as "Dyno Mill" manufactured by Shinmaru Enterprises), an attritor, a pearl mill (such as "DCP Mill" manufactured by Eirich), or a Coball mill; Wet jet mills (such as Genus PY, Sugino Machine Starburst, and Nanomizer), M-Technique Claire SS-5, and Nara Machinery Micros media-less dispersers; Other examples include, but are not limited to, roll mills, kneaders, etc. In addition, it is preferable to use a wet mixing device that has been treated to prevent metal from entering the device. When a media-type dispersing machine such as a ball mill is used, there is a risk that the structure of the active material may be destroyed by mixing, so a media-less dispersing machine is preferred.

[0051] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.

[0052] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.

[0053] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.

[0054] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.

[0055] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a non-aqueous solvent such as NMP, dropping the diluted fibrous carbon dispersion onto a substrate, drying the diluted fibrous carbon dispersion, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.

[0056] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and even more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be well and stably present without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass. The content of the fibrous carbon is preferably adjusted appropriately depending on the specific surface area of ​​the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc., so that a fibrous carbon dispersion liquid having appropriate fluidity or viscosity is obtained.

[0057] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.

[0058] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.

[0059] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.

[0060] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.

[0061] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.

[0062] The specific surface area of ​​fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and 2 / g or less is more preferable. The specific surface area of ​​the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of ​​the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.

[0063] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.

[0064] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.

[0065] When fibrous carbon is dispersed in a disperser that uses collisions with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon can break into short pieces. Carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.

[0066] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.

[0067] <Dispersant> The dispersant for the fibrous carbon dispersion is preferably one that can disperse and stabilize the fibrous carbon in the fibrous carbon dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to the fibrous carbon and can provide good dispersion stability. Depending on the characteristics required for dispersing the fibrous carbon, a suitable type of dispersant can be used in a suitable amount.

[0068] Examples of the resin-type dispersant that can be used include (meth)acrylic polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose derivatives, and copolymers thereof. Examples of the polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, and nitrile rubbers. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, and amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, and polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with acetal (acetoacetal-modified or butyral-modified, etc.) by aldehydes. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, ​​JP 2019-087304 A, Japanese Patent No. 6524479 A, ​​and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinylpyrrolidone, homopolymers of polyacrylonitrile, copolymers of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. A polymer having another substituent introduced into a part of the mer, a modified polymer, etc. may be used. The weight average molecular weight of the resin-type dispersant is preferably 500,000 or less, more preferably 300,000 or less, and preferably 3,000 or more, more preferably 5,000 or more, from the viewpoint of the affinity balance between the dispersed substance and the dispersion medium and the resistance to the electrolyte. The resin-type dispersant may be used alone or in combination of two or more kinds.

[0069] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, and Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Commercially available polyvinylpyrrolidone resins include, specifically, polyvinylpyrrolidone K30, K90 (manufactured by Fujifilm Wako), and K120 (manufactured by DSP Gokei Food & Chemical). Commercially available nitrile rubbers are available in various grades with different nitrile ratios, hydrogenation rates, and molecular weights under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and NipoleNBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used. Surfactants may be used in place of or in addition to the above-mentioned resin-type dispersants. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.

[0070] As the resin-type dispersant, a polymer containing at least an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit may be used. The aliphatic hydrocarbon structural unit of the polymer may contain an alkylene structural unit. The polymer may be hydrogenated.

[0071] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.

[0072] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, and an alkanetetrayl structural unit. Structural units containing a branch point, such as an alkanetriyl structural unit and an alkanetetrayl structural unit, are structural units different from structural units containing a branched alkylene structure and structural units containing a branched alkyl structure, which will be described later. The aliphatic hydrocarbon structural unit preferably contains at least an alkylene structural unit.

[0073] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.

[0074] <Dispersion medium> The dispersion medium of the fibrous carbon dispersion is not particularly limited, but is preferably a high dielectric constant solvent, and preferably contains one of the high dielectric constant solvents or a mixed solvent of two or more of them. In addition, the high dielectric constant solvent may be mixed with one or more other solvents.

[0075] High dielectric constant solvents include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, etc.) Amides, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclic (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethylsulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), water, and others such as tetrahydrofuran, urea, and acetonitrile can be used. The dispersion medium preferably contains an amide organic solvent or water, and the amide organic solvent more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent may be a value described in a solvent handbook or the like, and is preferably 2.5 or more at 20°C.

[0076] Examples of the method for removing the solvent and drying include hot air drying, vacuum drying, spray drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.

[0077] <Secondary battery electrode composite slurry> A slurry for a secondary battery electrode can be prepared using the composite for a secondary battery electrode. A composite slurry for a secondary battery electrode can be obtained by adding the composite for an electrode and a binder resin to a dispersion medium. If necessary, a fibrous carbon dispersion and other optional components may be appropriately contained within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination thereof. The optional components may be those described above for the fibrous carbon dispersion. The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material".

[0078] The solid content in the composite slurry is preferably 30% by mass or more, and more preferably 40% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 90% by mass or less, and more preferably 85% by mass or less.

[0079] The content of the electrode composite in the composite slurry is preferably 28% by mass or more, more preferably 38% by mass or more, and even more preferably 48% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 88% by mass or less, and more preferably 80% by mass or less.

[0080] The content of the binder resin in the composite slurry is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less. When the electrode composite contains a binder resin, it is preferable to adjust the total amount of the binder resin in the composite slurry to be within the above range.

[0081] The content of fibrous carbon in the composite slurry is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less. Since the electrode composite of the present invention contains fibrous carbon, it is preferable to adjust the total amount of fibrous carbon in the composite slurry to be within the above range. If the amount exceeds the above range, the charging of the active material in the electrode may become difficult. The amount of the charged material decreases, resulting in a lower capacity of the battery. Also, if the amount of the charged material is below the above range, the conductivity of the electrode and the battery may become insufficient.

[0082] <Method for producing secondary battery electrode composite slurry> In the method for preparing the composite slurry, the order of adding the electrode composite and the binder resin to the dispersion medium is not particularly limited. For example, a method of preparing the binder resin by adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition; a method of preparing the electrode composite by adding the binder resin to the dispersion medium and then adding the binder resin; a method of preparing the binder resin and the electrode composite by adding them all at once to the dispersion medium, and the like can be mentioned. As a method for preparing the composite slurry, a method of adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition and performing a stirring process is preferable. The stirring device used for stirring is not particularly limited. A disperser, a homogenizer, etc. can be used as the stirring device.

[0083] <Electrode for secondary batteries> The secondary battery electrode in the present invention includes a composite for secondary battery electrodes. The electrode may further include an optional component such as a dispersant. The electrode may be formed by preparing the above-mentioned composite slurry and applying the composite slurry, or by adding a binder or the like to the composite for secondary battery electrodes without using the composite slurry and forming each component into a sheet by pressing or the like. When the composite slurry is not used, a dry mixture that has been mixed in advance or a dried product after wet mixing may be used. When the composite slurry is used, for example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.

[0084] <Method of manufacturing secondary battery electrodes> The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0085] The method of applying the composite slurry onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.

[0086] The method for dry-mixing or wet-mixing each component by adding a binder or the like to the composite for secondary battery electrode without using a composite slurry is not particularly limited, and any known method can be used. Specifically, a dry / wet disperser described in the composite preparation method can be appropriately selected.

[0087] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0088] In the case where a binder or the like is added to the composite for a secondary battery electrode and each component is pressed into a sheet to form an electrode without using a composite slurry, each component obtained by adding a binder or the like to the composite for a secondary battery electrode, or the dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure-molded. A free-standing film made of a dry mixture or a dried product of a wet mixture may be prepared in advance and then laminated on the current collector. Alternatively, a current collector on which a resin thin film serving as a binder component has been formed in advance may be used or prepared.

[0089] Examples of the method for pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.

[0090] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.

[0091] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector, and the negative electrode may be an electrode film containing a negative electrode active material formed on a current collector.

[0092] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0093] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0094] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0095] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0096] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.

[0097] The secondary battery of the present invention is used in vehicles such as automobiles and portable electronic devices such as personal computers and smartphones. The battery can be suitably used as a battery for a device or the like. EXAMPLES

[0098] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0099] <Production of Dispersant> (Synthesis Example 1: Production of H-NBR) In a stainless steel polymerization reactor, 32 parts of acrylonitrile, 68 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.48 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3MPa, and hydrogenation reaction was carried out for 6 hours. After that, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solids were dried to obtain a dispersant (H-NBR). The Mooney viscosity (ML1+4, 100°C) of H-NBR (measured using an L-shaped rotor at a temperature of 100°C in accordance with Japanese Industrial Standard JISK6300-1) was 44. The hydrogenation rate (calculated from infrared spectroscopy by total reflection measurement method) was 0.7%. The structural unit derived from acrylonitrile determined from 1H-NMR quantitative spectrum was 32%.

[0100] (Synthesis Example 2: Production of polyacrylonitrile (PAN)) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile and substituted with nitrogen gas. The reaction vessel was heated to 70°C, and 90.0 parts of acrylonitrile, 10.0 parts of hydroxyethyl acrylate, and 2,2'-azobis(2,4 A mixture of 5.0 parts of 1,2-dimethylvaleronitrile (NOF Corp.; V-65) was added dropwise over 3 hours to carry out a polymerization reaction. After completion of the dropwise addition, the reaction was continued for another hour at 70°C, after which 0.5 parts of Perbutyl O was added and the reaction was continued for another hour at 70°C. Thereafter, the conversion rate was confirmed to be over 98% by measuring the non-volatile content, and the dispersion medium was completely removed by vacuum concentration to obtain a dispersant (polyacrylonitrile). The weight average molecular weight (Mw) of the polyacrylonitrile was 15,000.

[0101] In the examples and comparative examples, the following fibrous carbon was used. BT1001M: LUCAN BT1001M (LG Chem Ltd., multi-walled CNT, fiber diameter 10 nm) 100T: K-Nanos-100T (KUMHO PETROCHEMICAL, multi-walled CNT, fiber diameter 13.7 nm) 8S: JENOTUBE8S (JEIO, multi-walled CNT, fiber diameter 6.8 nm)

[0102] In the examples and comparative examples, the following active materials were used. NMC532:S740(LiNi 0.5 Mn 0.3 Co 0.2 O2, manufactured by RONBAY) SiOx: (SILICONMONOOXIDE, SiO 1.3C 5μm, manufactured by Osaka Titanium Technology Co., Ltd.)

[0103] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the materials and compositions shown in Table 1, a fibrous carbon dispersion was prepared as follows. First, NMP was placed in a stainless steel container and heated to 50°C. A dispersant was added while stirring with a disperser, and then the mixture was stirred for 1 hour to dissolve the dispersant. Next, fibrous carbon was added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON). Batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. At this time, the dispersion particle size confirmed by the grind gauge was 220 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The dispersion liquid was dispersed until the viscosity at 60 rpm measured with a B-type viscometer (TOKISANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa·s or less, and then the dispersion was subjected to 50 passes using a high-pressure homogenizer to obtain fibrous carbon dispersion 1.

[0104] (Production Examples 2 to 4) Fibrous carbon dispersions 2 to 4 were obtained in the same manner as in Production Example 1, except that the materials and compositions were changed according to Table 1.

[0105] [Table 1] The dispersants and additives listed in Table 1 are as follows. CMC1: Carboxymethylcellulose (Sunrose APP-84, manufactured by Nippon Paper Industries Co., Ltd.) NaOH: Sodium hydroxide (Tokyo Chemical Industry Co., Ltd., purity >98.0%, granular) PVA: Polyvinyl alcohol (Poval 203 manufactured by Kuraray) PVP: Polyvinylpyrrolidone (K-30, Fujifilm Wako Pure Chemical Industries, Ltd.)

[0106] (Production Examples 5 to 7) According to the composition shown in Table 1, fibrous carbon, dispersant, additives and dispersion medium were charged into a glass bottle, thoroughly mixed and dissolved or mixed, and then dispersed in a paint conditioner for 3 hours using 1.25 mmφ zirconia beads as a medium to obtain each fibrous carbon dispersion.

[0107] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 1 were mixed using a planetary mixer at a rotation speed of 30 rpm for 60 minutes to prepare a mixture. After that, the mixture was dried at 120°C for 2 hours in a hot air oven to obtain composite 1.

[0108] (Example 1-2) Composite 2 was obtained in the same manner as in Example 1-1, except that the rotation speed of the planetary mixer was changed to 50 rpm according to the composition shown in Table 2.

[0109] (Examples 1-3) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 1 were mixed using a planetary mixer at a rotation speed of 30 rpm for 60 minutes to prepare a mixture, and then the inside of the planetary mixer was vacuum-dried for 1 hour while running 80°C hot water through the jacket of the mixing vessel to obtain composite 3. Got it.

[0110] (Examples 1 to 4) According to the composition shown in Table 2, a mixture of NMC and fibrous carbon dispersion 1 was stirred at a rotation speed of 3000 rpm for 10 minutes using a high-shear multi-function machine Mechanofusion manufactured by Hosokawa Micron Co., Ltd. After that, it was dried in a hot air oven at 120°C for 2 hours to obtain Composite 4.

[0111] (Examples 1 to 5) According to the composition shown in Table 2, a mixture of NMC and fibrous carbon dispersion 1 was prepared by stirring at a rotation speed of 50 rpm for 15 minutes using a Trimix manufactured by Inoue Seisakusho. The mixture was dried at 120°C for 2 hours using a vacuum oven to obtain Composite 5.

[0112] (Examples 1-6 to 10) According to the composition shown in Table 2, NMC and fibrous carbon dispersions 2, 3, and 5 to 7 were mixed using a planetary mixer at a rotation speed of 30 rpm for 60 minutes to produce mixtures. After that, the mixtures were dried in an oven at 120°C for 2 hours to obtain composites 6 to 10.

[0113] (Examples 1-11 and 12) According to the composition shown in Table 2, SiOx and fibrous carbon dispersion 4 were mixed using a planetary mixer at a rotation speed of 50 rpm for 30 minutes to prepare a mixture. After that, the mixture was dried in an oven at 110°C for 2 hours to obtain composites 11 and 12.

[0114] (Examples 1 to 13) According to the composition shown in Table 2, NMC, fibrous carbon dispersion 1, and 11% binder solution (polyvinylidene fluoride resin: W#7200) dissolved in NMP in advance were stirred for 90 minutes at 60 rpm using a planetary mixer to prepare a mixture. After that, the inside of the container was kept at 80°C using a hot water chiller, and the pressure was reduced using a vacuum pump, and the mixture was dried for 2 hours to obtain composite 13.

[0115] (Examples 1-14) According to the composition shown in Table 2, NMC, fibrous carbon dispersion 1, and 11% binder solution (polyvinylidene fluoride resin: W#7200) dissolved in NMP in advance were mixed for 90 minutes using a high-speed mixer at an agitator speed of 500 rpm and a chopper speed of 1500 rpm to produce a mixture. After that, the inside of the container was kept at 80°C with a hot water chiller, and the mixture was dried for 2 hours under reduced pressure with a vacuum pump to obtain composite 14.

[0116] (Comparative Example 1-1) According to the composition shown in Table 2, NMC and fibrous carbon BT1001 were mixed for 10 minutes at 1000 rpm using a high shear multi-function machine Mechanofusion manufactured by Hosokawa Micron Corporation to obtain composite 15.

[0117] (Comparative Example 1-2) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 1 were weighed out into a container and stirred with a medicine spoon for 5 minutes to prepare a mixture. After that, it was dried at 120°C for 2 hours in a hot air oven to obtain composite 16.

[0118] (Comparative Example 1-3) According to the composition shown in Table 2, the fibrous carbon dispersion 1 and the solvent (NMP) were weighed out and placed in a stainless steel container, and NMC was added while stirring at 1000 rpm using a homogenizer MARKII 2.5 model manufactured by Primix Corporation, and then the mixture was stirred for 60 minutes to obtain a slurry. Using the slurry, a composite for secondary battery electrodes was produced using a spray dryer Mini Spray Dryer B-290 manufactured by Nippon Buchi Co., Ltd. The slurry was spray-dried at 220°C under closed system conditions (nitrogen atmosphere) using an inert loop B-295 to obtain composite 17.

[0119] (Comparative Examples 1-4) According to the composition shown in Table 2, SiOx and fibrous carbon BT1001 were mixed for 10 minutes at a rotation speed of 1000 rpm using a high-shear multifunction machine Mechanofusion manufactured by Hosokawa Micron Corporation to obtain composite 18.

[0120] (Comparative Examples 1-5) According to the composition shown in Table 2, the fibrous carbon dispersion 4 and water were weighed out and placed in a stainless steel container, and SiOx was added while stirring at 1000 rpm using a homogenizer MRKII2.5 manufactured by Primix Corporation, and then the mixture was stirred for 45 minutes to obtain a slurry. The slurry was spray-dried at 120°C using a spray dryer Mini Spray Dryer B-290 manufactured by Nippon Buchi Co., Ltd., to obtain a composite 19.

[0121] <Evaluation of the state of fibrous carbon in composites> The dispersion state of the fibrous carbon in the composite was determined using a JEOL JSM-7800F scanning electron microscope. · Criteria for determining carbon fiber aggregates [Average particle size of aggregates] ◎: Contains aggregates of fibrous carbon, with an average particle size of 0.2 μm to 3 μm ○: Fibrous carbon aggregates are included, and the average particle size is less than 0.2 μm or more than 3 μm ×: Fibrous carbon aggregates are not included [Average number of aggregates] ◎: Fibrous carbon aggregates were included, and the average number of fibrous carbon aggregates measured from 10 observation images at a magnification of 5,000 times was 2 or more. ◯: Fibrous carbon aggregates were included, and the number of fibrous carbon aggregates measured from 10 observation images at a magnification of 5,000 times was 0.5 or more and less than 2 on average. ×: No aggregates of fibrous carbon are included Criteria for determining the state of disintegration of the surface of fibrous carbon active material ◎: The area of ​​fibrous carbon adsorbed on the active material in a crushed state is 50% or more of the entire surface area of ​​the active material. ○: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 10% or more and less than 50% of the entire surface area of ​​the active material. ×: The fibers are not adsorbed to the active material in a crushed state.

[0122] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance, ThermoplusEV02TG8121, manufactured by Rigaku Co., Ltd. Compressed air was flowed at 200 mL / min, and the exothermic peak temperature obtained when the temperature was increased from 40°C to 800°C at a rate of 10°C / min was used as an index. The calculation of the exothermic peak temperature was performed by reading the rise of the exothermic peak of the fibrous carbon in the range of 400 to 700° C. in the DTA curve obtained by measurement, as shown in FIG.

[0123] <Powder resistance of composites> The powder resistivity of the composites was evaluated using a powder resistivity measurement system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd. Measurements were performed using a four-point probe method with a low-resistance powder probe, and the volume resistivity when a load of 20 kN was applied to each sample was used as an index. [Table 2]

[0124] <Preparation of positive electrode mixture slurry and positive electrode film> Capacity 150cm 3 In a plastic container, 8% binder solution (Polymer) previously dissolved in NMP was added. 14.2 parts of polyvinylidene fluoride resin (W#7200) and 11.1 parts of solvent (NMP) were weighed out, and then 74.7 parts of electrode composite 1 were added and stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain composite slurry 1. The non-volatile content of composite slurry 1 was 76 mass%.

[0125] Composites 2 to 10 and 15 to 17 were treated in the same manner as for composite slurry 1 to obtain composite slurries 2 to 10 and 15 to 17.

[0126] Capacity 150cm 3 7.0 parts of an 8% binder solution (polyvinylidene fluoride resin: W#7200) previously dissolved in NMP and 18.5 parts of a solvent (NMP) were weighed out into a plastic container, and then 74.5 parts of electrode composite 1 were added and stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain composite slurry 13. The non-volatile content of composite slurry 13 was 75 mass%.

[0127] The composite 14 was prepared in the same manner as the composite slurry 13 to obtain a composite slurry 14.

[0128] The composite slurries 1 to 10 and 13 to 17 were applied onto aluminum foil with a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to produce electrode films. The electrode films were then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain electrode films 1 to 10 and 13 to 17. The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling is 3.2 g / cm 3 It was.

[0129] <Preparation of negative electrode mixture slurry and negative electrode film> A plastic container was charged with 12.50 parts by mass of an aqueous solution containing 2% by mass of sodium carboxymethylcellulose (manufactured by Daicel FineChem Corporation, #1190) and 100 parts by mass of ion-exchanged water. 2.34 parts by mass were weighed out. Then, using a rotation-revolution mixer (Thinky Corporation, Awatori Rentaro, ARE-310), the mixture was stirred at 2000 rpm for 1 minute. Then, 2.44 parts by mass of electrode composite 11 was added, and using the same rotation-revolution mixer, the mixture was stirred at 2000 rpm for 5 minutes. Furthermore, 21.93 parts by mass of natural graphite (Nippon Graphite Industries Co., Ltd., CGB-20) was added. 0.78 parts by mass of an aqueous solution containing 48% by mass of styrene-butadiene emulsion was added and stirred at 2000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain composite slurry 11. The non-volatile content of the composite slurry was 48% by mass.

[0130] Composites 12, 18, and 19 were used to obtain composite slurries 12, 18, and 19 in the same manner as composite slurry 11.

[0131] The composite slurries 11, 12, 18, and 19 were applied onto copper foil with a thickness of 18 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to produce electrode films. The electrode films were then rolled using a roll press (Thank Metal, 3 t hydraulic roll press) to obtain electrode films 11, 12, 18, and 19. The weight per unit area of ​​the composite layer was 8 mg / cm. 2 The density of the composite layer after rolling is 1.6 g / cm 3 It was.

[0132] (Resistance of the positive electrode film) The volume resistivity of the electrode films 1 to 10 and 13 to 17 was measured by a four-probe method using Loresta GP (manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS-K7194. For the resistance measurement, a measurement electrode was used in which the coating substrate used in the preparation of each electrode was changed from aluminum foil to a PET substrate. A relative value (%) was determined based on the volume resistivity of the electrode film of Comparative Example 1-3, and evaluated according to the following criteria. Criteria for electrode resistance characteristics ◎: Over 200% (Excellent) ○: 150% or more but less than 200% (Excellent) ○△: 100% or more but less than 150% (good) △: 50% or more but less than 100% (defective) ×: Less than 50% (extremely poor)

[0133] (Resistance of the negative electrode film) The volume resistivity of the electrode films 11, 12, 18, and 19 was measured by a four-probe method using Loresta GP (manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS-K7194. For the resistance measurement, a measurement electrode was used in which the coating substrate used in the preparation of each electrode was changed from copper foil to a PET substrate. A relative value (%) was determined based on the volume resistivity of the electrode film of Comparative Example 1-5, and evaluated according to the following criteria. Electrode resistance characteristic criteria ○: 130% or more (Excellent) ○△: 100% or more but less than 130% (good) ×: Less than 100% (defective)

[0134] <Assembly of a cell for evaluating the positive electrode of a lithium-ion secondary battery> The previously prepared electrode films 1-10 and 13-17 were punched out to φ16 mm to be used as the working electrode, and a metallic lithium foil (thickness 0.15 mm) was used as the counter electrode. A separator (porous polypropylene film) was inserted and laminated between the working electrode and the counter electrode, and a bipolar sealed metal cell (Hosen HS Flat Cell) was assembled by filling it with an electrolyte (a non-aqueous electrolyte in which LiPF6 was dissolved at a concentration of 1M in a mixed solvent in which ethylene carbonate and diethyl carbonate were mixed at a volume ratio of 1:1). The cell was assembled in a glove box substituted with argon gas.

[0135] <Evaluation of rate characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus fabricated was placed in a constant temperature room at 25°C and subjected to charge / discharge Charge and discharge measurements were performed using a constant current / constant voltage charger (Hokuto Denko Corporation, SM-8). The charge rate was 0.2 C, the charge end voltage was 4.2 V, and the charge was constant current / constant voltage charge (cutoff current: 0.02 C). After that, constant current discharge was performed at a discharge rate of 0.2 C with a discharge end voltage of 2.5 V. This operation was repeated three times, and then constant current constant voltage charging (cutoff current: 0.02 C current) was performed at a charge rate of 0.2 C with a charge end voltage of 4.2 V, and then discharged at a discharge rate of 3 C with a discharge end voltage of 2.5 V. A constant current discharge was performed at 1C. 1C was defined as the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The rate characteristics can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, using the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 0.2C discharge capacity x 100 (%) The relative value (%) was calculated based on the rate characteristic of Comparative Example 1-3, and evaluated according to the following criteria. Rate characteristic criteria ◎: 150% or more (very good) ○: 130% or more but less than 150% (Excellent) ○△: 100% or more but less than 130% (good) ×: Less than 100% (defective)

[0136] <Evaluation of cycle characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus fabricated was placed in a constant temperature room at 25°C and subjected to charge / discharge Charge and discharge measurements were performed using a constant current / constant voltage charger (Hokuto Denko Corporation, SM-8). The charge rate was 0.2 C, the charge end voltage was 4.2 V, and the charge was constant current / constant voltage charge (cutoff current: 0.02 C). After that, constant current discharge was performed at a discharge rate of 0.2 C and a discharge end voltage of 2.5 V. This operation was repeated 200 times. 1 C was defined as the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 200th 0.2C discharge capacity, as shown in Equation 2 below. (Formula 2) Cycle characteristic = 3rd 0.2C discharge capacity / 200th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristics of Comparative Example 1-3, and the cycle characteristics were evaluated according to the following criteria. ◎: 180% or more (excellent) ○: 150% or more but less than 180% (Excellent) ○△: 100% or more but less than 150% (good) ×: Less than 100% (defective)

[0137] <Assembly of a cell for evaluating the negative electrode of a lithium-ion secondary battery> The previously prepared electrode films 11, 12, 18, and 19 were punched out to φ16 mm to be used as working electrodes, and a metallic lithium foil (thickness 0.15 mm) was used as a counter electrode. A separator (porous polypropylene film) was inserted and laminated between the working electrode and the counter electrode, and an electrolyte (a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 3:5:2 (volume ratio) was prepared, and VC (vinylene carbonate) and FEC (fluoroethylene carbonate) were added as additives to 100 parts by mass of the mixed solvent, and then LiPF6 was dissolved at a concentration of 1M to form a non-aqueous electrolyte) was filled to assemble a bipolar sealed metal cell (Hosen HS Flat Cell). The cell was assembled in a glove box substituted with argon gas.

[0138] <Evaluation of rate characteristics of negative electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery negative electrode evaluation cell thus fabricated was placed in a constant temperature room at 25°C and subjected to charge / discharge Charge and discharge measurements were performed using a device (Hokuto Denko Corporation, SM-8). Constant current and constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 0.05V. After that, constant current discharge was performed at a discharge rate of 0.2C with a discharge end voltage of 1.5V. This operation was repeated three times, and then constant current constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 0.05V, and then discharged at a discharge rate of 3C with a discharge end voltage of 1. A constant current discharge was performed at 5 V. 1 C was the current value at which the theoretical capacity of the negative electrode was charged or discharged in 1 hour. The rate characteristic is the ratio of the 0.2 C discharge capacity to the 3 C discharge capacity, and can be expressed by the following formula 2. can. (Formula 2) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the rate characteristics of Comparative Examples 1-5, and was evaluated according to the following criteria. ◎: 150% or more (very good) ○: 100% or more but less than 150% (Excellent) ×: Less than 100% (defective)

[0139] <Evaluation of cycle characteristics of negative electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery negative electrode evaluation cell thus fabricated was placed in a constant temperature room at 25°C and subjected to charge / discharge Charge and discharge measurements were performed using a device (Hokuto Denko Corporation, SM-8). Constant current and constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 0.05V. After that, constant current discharge was performed at a discharge rate of 0.2C with a discharge cut-off voltage of 1.5V. This operation was repeated 20 times. 1C was defined as the current value at which the theoretical capacity of the negative electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 20th 0.2C discharge capacity, using the following formula 1. (Formula 1) Cycle characteristic = 3rd 0.2C discharge capacity / 20th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristics of Comparative Examples 1 to 5, and the results were evaluated according to the following criteria: ⊚: 150% or more (very good) ○: 100% or more but less than 150% (Excellent) ×: Less than 100% (defective) [Table 3]

[0140] As shown in Table 3, the battery characteristics of the embodiment were superior to those of the comparative example. As shown in the example of Figure 2, when the fibrous carbon in the composite is in an appropriate state, it is possible to form a uniform conductive path within the electrode, which is presumably responsible for reducing the electrode resistance and ensuring that the active material in the electrode is used evenly and uniformly in the charge and discharge reactions, leading to improved rate characteristics and cycle characteristics. From the above, it was demonstrated that an electrode composite within the range of the present invention can exhibit excellent battery characteristics.

Claims

1. A composite for a secondary battery electrode comprising an electrode active material and fibrous carbon, A composite for a secondary battery electrode, characterized in that a portion of the fibrous carbon has a crushed form and adheres to a surface of the electrode active material, and a portion of the fibrous carbon has an aggregate form.

2. 2. The composite for a secondary battery electrode in accordance with claim 1, wherein the average particle size of said aggregates is from 0.2 μm to 50 μm.

3. 3. The composite for a secondary battery electrode according to claim 1, wherein the fibrous carbon has an exothermic peak temperature of 550° C. or lower as determined by simultaneous thermogravimetry-differential thermal analysis in the presence of oxygen.

4. 3. The composite for a secondary battery electrode according to claim 1, further comprising a binder resin.

5. 3. A secondary battery electrode comprising the composite for a secondary battery electrode according to claim 1 or 2.

6. A secondary battery comprising the electrode for a secondary battery according to claim 5 .

7. A vehicle or device comprising the secondary battery according to claim 6.

8. A method for producing the composite for a secondary battery electrode according to claim 1, A method for producing a composite for a secondary battery electrode, comprising the steps of: combining a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent with an electrode active material using a mixing device; and removing the solvent and drying the resulting mixture.

Citation Information

Patent Citations

  • Hydraulic clutch switch valve

    JP1978077946A

  • Optical processing apparatus

    JP1988080526A

  • Active material and battery using the same

    JP2016201228A

  • Lithium nickelate-carbon composite positive electrode active material particle powder, and manufacturing method thereof, and nonaqueous electrolyte secondary battery

    JP2017142997A